Determinants affecting the purchase intention of foreign brands among selected millennials in Kuala Lumpur / Siti Nur Ain Salih - Salih, Siti Nur Ain (Faculty of Business and Management, 2019)
Foreign brands has always been empowering local industry since before because of the marketing strategy that is appropriate. Therefore, the objective for this study was to identify the determinants affecting millennials’ purchase intention of foreign brands. The determinants was proposed based on the previous studies to examine the relationship between corporate social responsibilities, social media marketing and sales promotion towards purchase intention of foreign brands among selected millennials in Kuala Lumpur. Total 278 sample of respondent data has been recorded and being analysis for this study. Data has been analysing by using Statistic Package for Social Science (SPSS). Regression and correlation used in this study analyses the relationship of independent variables toward dependent variable.